INFLUENCE OF UPBJJ-UT IMAGE AND STUDENT SATISFACTION ON LOYALTY OF UT STUDENTS - Mujadi, Mujadi (IJRDO - Journal of Social Science and Humanities Research, 2018)
The long distance higher education system (PTJJ) opens access to education for anyone, anywhere, anytime. Through various legal instruments issued by the government, namely Minister of National Education Decree No.U / 2001, National Education System Law No. 20/2003, PP 17/2010, and also PP 66/2010, the PJJ system has become an integral part of the world of education in Indonesia, and is an option for people to gain access to education. PJJ has the characteristics of open, independent, complete learning, using information and communication technology (ICT), and / or using other technologies. This paper discusses the influence of UPBJJ-UT Jayapura’s image on UT student satisfaction and loyalty. Intensive promotion was carried out through newspapers, TV, Roadshow / talk shows and performances of both educational exhibitions. UT Jayapura’s imagery is very effective through the rest of the word of mouth from others causing the UT Jayapura brand to be easily identified. Other positive images are professionals in service and availability of infrastructure, service to all segments of students and prospective students gives a high sense of empathy between officers and students and prospective students; high levels of consumer confidence are netted through speed in the process of registration services, optimal and standard face-to-face tutorial services, convenient exam services, and responsiveness and empathy of staff / officers in responding to all student complaints. In terms of loyalty, the establishment of an emotional and kinship relationship between active and alumi students with regional responsibility, creating a harmonious positive relationship and increasing consumer loyalty